Capital Gains Taxes and Realizations: Evidence from Interstate Comparisons - Bogart, William T.; Gentry, William M. (The Review of Economics and Statistics, 1995)
This paper documents the interstate variation in capital gains taxation and examines the relation between the marginal tax rate on capital gains and aggregated state-level realizations between 1979 and 1990. Using state-level aggregated data, rather than data on individual taxpayers, alleviates the problem that the marginal tax rate is endogenous to the amount of capital gains realized. The estimated elasticity of realizations with respect to the tax rate is -0.65, smaller than that found by most researchers using panel data. This finding is robust to a variety of alternative specifications. Copyright 1995 by MIT Press.